Penerapan Model Pembelajaran Kooperatif Tipe Round Table untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Pokok Bahasan Segitiga Kelas VII SMP Negeri 2 Pasirian Tahun Ajaran 2015/2016 - Mahanurani, Idawati; Setiawan, Toto' Bara; Oktavianingtyas, Ervin (Kadikma, 2016)
Abstract Education is a necessity for every human being. There are many components that support, among others: teachers, students, curriculum used and others. Teachers are the determinants of the success of a learning system. Therefore, teachers should understand the model, method, setrategi, or approach of learning. One of the learning model that can be applied is cooperative learning model Round Table type. The purpose of this research is to improve students activity and learning achievement for the triangle subject in VII-D SMP Negeri 2 Pasirian. The result showed that the percentage of student activity from 74,70% in cycle I to 86,97% in cycle II. The result of student learning showed an increase from 60,60% of students who completed in cycle I to 75,76% student which complete in cycle II. From these results indicate that the implementation of Round Table can improve student activity and learning outcomes and can be used as an alternative method of learning in the classroom. Keywords: cooperative, round table, students' activities and achievement